Spiders of the genus Phycosoma O. P.-Cambridge, 1879 (Araneae: Theridiidae) from Hainan Island, China - Zhang, Feng; Zhang, Bao-Shi (Zootaxa, 2012)
Nine species of the theridiid spider genus Phycosoma are reported from Hainan Island, China, including two new species:Phycosoma digitula n. sp. (male, female) and P. diaoluo n. sp. (male). P. stellaris (Zhu, 1998) n. comb., P. hana (Zhu,1998) n. comb., P. labialis (Zhu, 1998) n. comb., P. hainanensis (Zhu, 1998) n. comb. and P. sinica (Zhu, 1992) n. comb.are transferred from the genus Dipoena Thorell, 1869. The males of P. stellaris, P. hana and P. labialis are described andillustrated here for the first time. P. amamiense (Yoshida, 1985) is recorded from Hainan Island for the first time; P. martinae (Roberts, 1983) is also included in this paper.